Analysis of pH Changes in Cassava Fermentation Process Exposed to ELF Magnetic Fields Intensity 100????T, 200????T and 300????T - Siti Magfirah; Trapsilo Prihandono; Sudarti Sudarti (Universitas Insan Cendekia Mandiri, 2022)
ELF (Exemelly Low Frequency) is a spectrum of electromagnetic waves with a frequency of less than 300 Hz. This study aims to determine the effect of exposure to the ELF magnetic field on the degree of acidity (pH) in the maturation process of cassava tape. The research method used is a true experiment, namely by giving exposure to the ELF magnetic field in the experimental group and not giving exposure to the ELF magnetic field in the control group. Exposure to the ELF (Extremely Low Frequency) magnetic field on cassava tape used intensities of 100????T, 200????T, and 300????T with various exposure times, namely 30 minutes, 60 minutes, and 90 minutes. The type of research used is experimental research with a completely randomizedidesign (CRD) which aims to examine the effect of treatment by repeating the experiment. Data collection was carried out after the 1st day to the 4th day. The results showed that exposure to ExtremelyiLowiFrequencyi(ELF) magnetic fields can affect the average pH value in the cassava tape fermentation process which is shown through variations in the bar chart. The experimental group samples (E100????T 60') and (E300????T 30') on day 1 to day 4 there was a significant change in pH value.